(untitled) (Bangladesh Journal of Psychiatry, 2022)
Chronic illnesses, such as Parkinson’s disease, are often associated with a wide variety of psychiatric illnesses such, somatic symptom disorder. The presentation and severity of complaints associated with somatic symptoms vary, but rarely do they cause the patient such distress that they attempt to commit suicide, as a result of being unable to cope with the discomfort. In such cases, there is a diagnostic dilemma of whether these are cases of somatic symptom disorder or mood disorder. Herein, we will discuss a case where a 65 year old retiree, suffering from Parkinson’s disease was admitted this in hospital, after multiple suicide attempts. We eventually excluded major depressive disorder as a diagnosis, and we treated the patient as a case of somatic symptom disorder. He was treated with selective nor-epinephrine reuptake inhibitor and psychotherapy (including relaxation therapy), with which he responded well. The case report supports previous studies which have found that medication and psychotherapy aid in the improvement of the condition of such patients. Bang J Psychiatry 2022;36(1):21-23